The human gut microbiota and its interactive connections to diet. Issue 5 (10th May 2016) - Milani, C.; Ferrario, C.; Turroni, F.; Duranti, S.; Mangifesta, M.; van Sinderen, D.; Ventura, M.
Abstract: The microbiota of the gastrointestinal tract plays an important role in human health. In addition to their metabolic interactions with dietary constituents, gut bacteria may also be involved in more complex host interactions, such as modulation of the immune system. Furthermore, the composition of the gut microbiota may be important in reducing the risk of contracting particular gut infections. Changes in the microbiota during an individual's lifespan are accompanied by modifications in multiple health parameters, and such observations have prompted intense scientific efforts aiming to understand the complex interactions between the microbiota and its human host, as well as how this may be influenced by diet.